Optimization of Teller Services Using Queuing Theory at XYZ Bank - Krisna, Daffandri Dwi; Sumiati, Sumiati (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
Bank XYZ is one of the largest state-owned banks in Indonesia that provides various financial services. Currently Bank XYZ has 3 teller services only. This study aims to determine the use of customer queuing schemes currently used in XYZ bank teller services. The data processed is the arrival of customers who transact at the teller area of Bank XYZ. This study uses the Queuing Theory method with the M / M / S (Multiple Channel Single Phase) model and also uses FlexSim software. Then analyze with the addition of the number of tellers (services). Finally, a comparison is made between manual and software calculation methods. Based on the results of the data analysis, the optimal improvement in the application of the queuing system is to add 1 teller service to 4 teller services. The improvement in the performance of the queuing system is characterized by a reduction in the number of customers in line at peak hours 10.00 - 11.00 which initially amounted to 11 people reduced to 3 people and the average waiting time of customers in the queue from 10.08 minutes to 4.02 minutes. Therefore, optimal queuing system performance can be ensured by increasing the number of tellers to four.